Maiestas principum : Herzogsurkunden als Medien der Herrschaftsrepräsentation in Schlesien, Pommern und Pommerellen (1200-1325). - Rossignol, Sébastien (Quellen und Studien des Deutschen Historischen Instituts Warschau., 2019)
Medieval ruler's charters have been understood in historical research since Heinrich Fichtenau as a medium of princely propaganda. Particular attention was paid to the conveyance of visual impressions through the documents or the presentation of various aspects of rule and authority in specific components, especially in the areas of the document forms. The present study by Sébastien Rossignol is dedicated to the reconstruction of reception processes in medieval documents, which has so far been neglected in research. Representation is understood here as a communication process that can only be meaningfully realized if several communicators participate in the process. The question of why and how, by whom and for whom medieval documents were used to represent power is the focus of the present study. The Intitulationes, the Arengen and, in Peter Rück's words, the "visual rhetoric" of the sovereign documents of Silesia, Pomerania and Pomerania up to the beginning of the 14th century are examined. In order to emphasize the process of representation, the conception of means of representation, their message and their contemporary Perception socially and culturally contextualized.